2013
DOI: 10.1371/journal.pone.0078095
|View full text |Cite
|
Sign up to set email alerts
|

Non-Essential Role for TLR2 and Its Signaling Adaptor Mal/TIRAP in Preserving Normal Lung Architecture in Mice

Abstract: Myeloid differentiation factor 88 (MyD88) and MyD88-adaptor like (Mal)/Toll-interleukin 1 receptor domain containing adaptor protein (TIRAP) play a critical role in transducing signals downstream of the Toll-like receptor (TLR) family. While genetic ablation of the TLR4/MyD88 signaling axis in mice leads to pulmonary cell death and oxidative stress culminating in emphysema, the involvement of Mal, as well as TLR2 which like TLR4 also signals via MyD88 and Mal, in the pathogenesis of emphysema has not been stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…In support of our previous report, in which we detected increased Nox3 in TLR4 -/mice, Ruwanpura et al reported that elevated oxidative protein carbonylation levels and increased numbers of alveolar cell apoptosis were detected in TLR4 -/mice, along with upregulation of Nox3 mRNA expression (23). Our studies of double TLR4 -/-/Nox3 -/mice demonstrate for the first time in vivo that Nox3 mediates, at least in part, the lung injury phenotype of TLR4 -/mice.…”
Section: Discussionsupporting
confidence: 91%
“…In support of our previous report, in which we detected increased Nox3 in TLR4 -/mice, Ruwanpura et al reported that elevated oxidative protein carbonylation levels and increased numbers of alveolar cell apoptosis were detected in TLR4 -/mice, along with upregulation of Nox3 mRNA expression (23). Our studies of double TLR4 -/-/Nox3 -/mice demonstrate for the first time in vivo that Nox3 mediates, at least in part, the lung injury phenotype of TLR4 -/mice.…”
Section: Discussionsupporting
confidence: 91%
“…Aberrant expression of RAGE in the lung, irrespective of whether it is increased or decreased, is associated with abnormal lung morphogenesis, airspace enlargement and the development of emphysema‐like pathology 7,38‐42 . Moreover, TLR4 −/− mice develop emphysema as they age, largely as a result of increased oxidant generation and elastolytic activity 43,44 . Thus, collectively, the current evidence indicates important roles for RAGE and TLR4 in maintaining lung homeostasis, structure and function and further emphasizes the need to better understand the role of these receptors in the lung, both in health and disease.…”
Section: Discussionmentioning
confidence: 91%
“…7,[38][39][40][41][42] Moreover, TLR4 −/− mice develop emphysema as they age, largely as a result of increased oxidant generation and elastolytic activity. 43,44 Thus, collectively, the current evidence indicates important roles for RAGE and TLR4 in maintaining lung homeostasis, structure and function and further emphasizes the need to better understand the role of these receptors in the lung, both in health and disease.…”
Section: Discussionmentioning
confidence: 98%
“…Given that TLR2 and TLR4 have been previously shown to play roles in mediating pulmonary oxidative stress (32,61,83,109), we also profiled the mRNA expression of NADPH oxidase (Nox)1, Nox2, Nox3, Nox4, NAD(P)H quinone dehydrogenase (Nqo)1, nuclear factor (erythroid-derived 2)-like-2 factor (Nrf2), glutamate-cysteine ligase catalytic subunit (Gclc), glutathione peroxidase (Gpx)2, heme oxygenase (Hmox)1 and glutathione Stransferase pi (Gstp)1 ( Figure 6J-S). CS exposure induced the expression of Nox2 ( Figure 6K) and suppressed Gstp1 ( Figure 6S), whilst other genes were not altered in Tlr2 -/or Tlr4 -/mice compared to WT controls.…”
Section: Cs-induced Pulmonary Inflammation Was Largely Unaltered In Tmentioning
confidence: 99%